Desmoglein-4 Deficiency Exacerbates Psoriasiform Dermatitis in Rats While Psoriasis Patients Displayed a Decreased Gene Expression of DSG4 - Moreno-Sosa, Tamara; Sánchez, María Belén; Pietrobon, Elisa Olivia; Fernandez-Muñoz, Juan Manuel; Zoppino, Felipe Carlos Martín; Neira, Flavia Judith; Germanó, María José; Cargnelutti, Diego Esteban; Innocenti, Alicia Carolina; Jahn, Graciela Alma; Valdez, Susana Ruth; Mackern-Oberti, Juan Pablo (Frontiers in Immunology, 2021)
Desmogleins are involved in cell adhesion conferring structural skin integrity. However, their role in inflammation has been barely studied, and whether desmoglein-4 modulates psoriasis lesions is completely unknown. In this study, we assessed the impact of desmoglein-4 deficiency on the severity of imiquimod (IMQ) induced skin inflammation and psoriasi-form lesions. To this end, desmoglein-4-/- Oncins France Colony A (OFA) with Sprague Dawley (SD) genetic background were used. Additionally, human RNAseq datasets from psoriasis (PSO), atopic dermatitis (AD), and a healthy cohort were analyzed to obtain a desmosome gene expression overview. OFA rats displayed an intense skin inflammation while SD showed only mild inflammatory changes after IMQ treatment. We found that IMQ treatment increased CD3+ T cells in skin from both OFA and SD, being higher in desmoglein-4 deficient rats. In-depth transcriptomic analysis determined that PSO displayed two-fold less DSG4 expression than healthy samples while both, PSO and AD. Although, underlying mechanisms are still unknown, these results suggest that the lack of desmoglein-4 may contribute to immune mediated skin disease progression, promoting leukocyte recruitment to skin. Although further research is needed, targeting desmoglein-4 could have a potential impact on designing new biomarkers for skin diseases.